2012
DOI: 10.1007/s12034-012-0276-8
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse phase transition, piezoelectric and optical study of Bi0·5Na0·5TiO3 ceramic

Abstract: Bismuth sodium titanate, Bi 0•5 Na 0•5 TiO 3 (BNT) is considered to be an excellent candidate for a key material of lead-free dielectric ceramics. In this study, we propose the dielectric and optical study of single phase BNT powder prepared by solid-state reaction route. The phase formation and structural study were done by X-ray diffraction (XRD) which shows well developed crystallite with a pure perovskite phase. The ceramic was sintered at different temperatures from 1050 • C to 1175 • C to study the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…The interpolated bandgap of samples sintered at 500 C and 1000 C is 3.01 eV and 3.14 eV, respectively. These values are in a good agreement with previous reports in which the bandgap of Bi 0.5 Na 0.5 TiO 3 varies in range of 2.82-2.94 eV [8][9][10][11][12].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The interpolated bandgap of samples sintered at 500 C and 1000 C is 3.01 eV and 3.14 eV, respectively. These values are in a good agreement with previous reports in which the bandgap of Bi 0.5 Na 0.5 TiO 3 varies in range of 2.82-2.94 eV [8][9][10][11][12].…”
Section: Resultssupporting
confidence: 93%
“…The theoritical calculation for Bi 0.5 Na 0.5 TiO 3 suggests this material has a wide direct bandgap of 1.97 eV [7]. The experimental results from Parija et al show that the bandgap is around 2.94 eV [8]. Another suggestion from Wang et al is that the bandgap varies in a range of 2.82 eV and 2.92 eV, depending on the concentration of NaOH in hydrothermalization [9].…”
Section: Introductionmentioning
confidence: 99%
“…The band gap energy (E g ) was associated with the absorbance and photon energy by following equation hγ α ∝ (hγ -E g ) n , where α is the absorbance, h the Planck constant, γ the frequency, E g the optical band gap and n a constant associated with different types of electronic transition (n = 1/2, 2, 3/2 or 3 for direct allowed, indirect allowed, direct forbidden and indirect forbidden transitions, respectively). 32 Thus, the E g values of BNKTS-100xLi ceramics were evaluated by extrapolating the linear portion of the curve or tail. Our results indicated that an indirect transition which occurred because of n = 2, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Parija et al pointed out that the obtained E g value of 2.94 eV for the Bi 0.5 Na 0.5 TiO 3 ceramics can be associated to a structural order-disorder effect into the lattice due to a symmetry break between the O-Ti-O bonds and/or distortions on the (TiO 6 ) clusters. 32 Lee et al reported the strong relation between band gap and the tolerance factor in various solid solution ABO 3 -A'B'O 3 . 33,34 Levin et al suggested that the dominant effect of the local displacements on band-gap values due to strong O 2p-Ti 3d hybridization.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the average grain size increases with increasing the sintering temperature. Parija et al [18] and Aman et al [16,17] have concluded that lower sintering temperature with longer sintering time produce smaller grain size ceramics, and also the densification behavior of the NBT ceramics at different sintering temperatures can be explained in terms of defect chemistry and the creation of oxygen vacancies. Aman et al [16,17] also have measured the effect of temperature on NBT-based ceramics, and optimized the sintering temperature to get highly dense and fine microstructural ceramics.…”
Section: Xrd and Structural Propertiesmentioning
confidence: 99%